Effects of cobalt doping on structural, morphological, and optical properties of Zn2SiO4 nanophosphors prepared by sol-gel method - Mohd Rasdi, Norhafizah; Yap, Wing Fen; Sheh Omar, Nur Alia; Azis, Raba'ah Syahidah; Mohd Zaid, Mohd Hafiz (Elsevier, 2017)
In this paper, undoped and cobalt (II) (3, and 5 mol %) doped zinc silicate nanophosphors prepared by a sol-gel method which were heated at 1000 °C were studied in detail. From the XRD result, undoped and Co2+ doped zinc silicate sample yields α- and β-Zn2SiO4. This also shows that α-Zn2SiO4 acts as the primary phase in the crystal structure of the sample. For FESEM, the grain size decreases as the dopant increases where undoped sample indicates average grain size of 181 nm while 3 and 5 mol % exhibits containing ones 136.89 nm and 176.22 nm respectively. With FTIR transmission a major peak at range of 1100 cm−1, 880, 550, and 350 assigning as Si-O-Si asymmetric stretching, SiO4 asymmetric stretching, ZnO4 symmetric stretching, and Si-O asymmetric deformation vibration were observed respectively. The absorption band of doped Zn2SiO4 exhibited a higher absorbance intensity in the UV region compared to undoped Zn2SiO4. Besides, all the samples depict that the sample was having a red shift in which the band shifted to the longer wavelength. The energy band gap value of undoped sample shows 3.07 eV and when Co2+ dopant (3 and 5 mol %) was introduced, the energy band gap started to decrease (2.46 and 2.42 eV respectively). PL emission presents two peaks at blue emissions (420 and 480 nm) and a green emission (525 nm). The result present that Co2+:Zn2SiO4 is potentially good to use as blue and green phosphors for luminescent optical material.